A Test of the 'Krugman Hypothesis' for the United States, Britain, and Western Germany - Patrick A. Puhani (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2003)
Rising wage inequality in the U.S. and Britain (especially in the 1980s) and rising continental European unemployment (with rather stable wage inequality) have led to a popular view in the economics profession that these two phenomena are related to negative relative demand shocks against the unskilled in the industrialised world, combined with flexible wages in the Anglo-Saxon countries, but institutional rigidities in continental Europe (?Krugman hypothesis?). An alternative view stresses the importance of differing supply changes across countries. However, empirical evidence on these questions is sparse. Furthermore, existing international comparisons often rely on strong assumptions or compromise on data quality. This paper uses large data sets from the U.S., Britain, and western Germany to test the Krugman hypothesis for the 1990s, when unemployment in Germany increased (unlike in the U.S. and Britain, where it fell). British and German evidence is further backed up with alternative data sets for these countries. I find evidence for the Krugman hypothesis when Germany is compared to the U.S. However, supply changes differ considerably between countries, with especially Britain experiencing enormous increases in the relative supply of skills and a relatively constant skill premium.
Keywords: E24; J21; J31; J64; 330; wage; earnings; unemployment; non-employment; rigidity; identification; Lohnstruktur; Arbeitslosigkeit; Ungelernte Arbeitskräfte; Arbeitsnachfrage; Schock; Lohnrigidität; Schätzung; Vereinigte Staaten; Großbritannien; Deutschland